The Influence of Senior Mentoring on the Adaptation Process of New Students: A Case Study at the Faculty of Teacher Training and Education, Lambung Mangkurat University - Elmy, Muhammad; Maftuh, Bunyamin; Kiptiah, Mariatul; Hakam, Kama Abdul (FKIP - Universitas Riau, 2025)
This study examines the relationship between senior mentoring programs and the adaptation process of first-year university students. Using a qualitative phenomenological approach, in-depth interviews were conducted with first-year students who participated in a structured senior mentoring program. The findings reveal that consistent interactions, effective communication, and role modeling from senior mentors significantly enhance both academic and social integration among new students. Mentoring not only helps students understand academic systems and manage learning challenges but also fosters self-confidence, a sense of belonging, and emotional attachment to the campus environment. However, the effectiveness of the program is strongly influenced by the quality of the mentor–mentee relationship, the mentor's empathy, and institutional support through training and monitoring systems. The study recommends that higher education institutions design mentoring programs with clear structures, provide communication and leadership training for mentors, and ensure appropriate mentor–mentee matching to optimize adaptation outcomes. These findings contribute to the growing body of literature on peer mentoring and student retention, offering practical insights for improving student engagement and reducing dropout rates in the first year.